Natural laminar flow airfoil shape design at transonic regimes with multi-objective evolutionary algorithms. (March 2019) - Chen, Yongbin; Tang, Zhili
The natural laminar flow airfoil shape design at transonic regime is solved using multi-objective evolutionary algorithms in this paper. A shock wave control bump is used to reduce wave drag of natural laminar flow airfoil in transonic flow, and the e N transition prediction method based on the linear stability theory is used to predict the transition location. The multi-island parallel multi-objective evolutionary algorithms is implemented to optimize the airfoil shape equipped with shock wave control bump for obtaining a larger laminar flow region and a weaker wave drag simultaneously. Optimization experiment shows that it is easy to capture the Pareto front of wave drag minimization and laminar flow region maximization. Results demonstrate that both wave drag and friction drag performance of several chosen Pareto members are significantly improved via the optimal airfoil shape and shock wave control bump device compared to that of the baseline shape.